Propriedades Físicas do Semicondutor Bi2Te3 - Alves, Edvaldo de Oliveira (2007)
Thermoelectric Refrigerators (TEC Thermoelectric Cooling) are solid-state heat pumps used in applications where stabilization of temperature cycles or cooling below the room temperature are required. TEC are based on thermoelectric devices, and these in turn, are based on the Peltier effect, which is the production of a difference in temperature when an electric current is applied to a junction formed by two non-similar materials. This is one of the three thermoelectric effects and is a typical semiconductor junction phenomenon. The thermoelectric efficiency, known as Z thermoelectric or merit figure is a parameter that measures the quality of a thermoelectric device. It depends directly on electrical conductivity and inversely on the thermal conductivity. Therefore, good thermoelectric devices have typically high values of electrical conductivity and low values of thermal conductivity. One of the most common materials in the composition of thermoelectric devices is the semiconductor bismuth telluride (Bi2Te3) and its alloys. Peltier plates made up by crystals of semiconductor P-type and N-type are commercially available for various applications in thermoelectric systems. In this work, we characterize the electrical properties of bismuth telluride through conductivity/resistivity of the material, and X-rays power diffraction and magnetoresistance measurements. The results were compared with values taken from specific literature. Moreover, two techniques of material preparation, and applications in refrigerators, are discussed